The mental health of athletes: recreational to elite - Reardon, C. L. (Current Sports Medicine Reports, 2021)
Athletes at all levels of competition are susceptible to mental health symptoms and disorders, and this has been a topic of increased research attention in recent years. The most common such conditions will be highlighted in this article, with a clinical focus on unique aspects of presentation, diagnosis, and management among athletes. Conditions addressed include depression, anxiety and related disorders, eating disorders, sleep concerns, attention-deficit/hyperactivity disorder, bipolar and psychotic disorders, and substance use disorders and behavioral addictions. Athletes experience particular physiologic and psychosocial demands that impact how they present symptomatically and how treatment modalities, including psychotherapy and pharmacologic treatments, impact them.